Oil-based cyclo-oligosaccharide nanodevices for drug encapsulation - Jennifer Noro (2017)
New encapsulation nanodevices were synthesized by emulsification of cyclo-oligosaccharides fully substituted by hydrophobic palmitic chains. These highly hydrophobic compounds, acquire oily-like behaviour at moderate temperatures (50 °C) and when submitted to ultrasounds (US) can undergo emulsification. The improved emulsifying properties of modified cyclo-oligosaccharides are suitable to produce small and narrow sized nanoemulsions with ability to encapsulate amphiphilic molecules. Both encapsulation and delivery of a therapeutic drug, methotrexate (MTX), with amphiphilic character was assessed. The physicochemical properties of the cyclo-oligosaccharide nanoemulsions containing MTX were investigated by nuclear magnetic resonance (NMR), scanning transmission electron microscopy (STEM) and dynamic light scattering (DLS). The results revealed that the modified cyclo-oligosaccharides are potential platforms for the encapsulation of bio compounds for cosmetic and pharmaceutical purposes.